Toys! : amazing stories behind some great inventions - Wulffson, Don L. (New York : H. Holt, 2000)
Describes the creation of a variety of toys and games, from seesaws to Silly Putty and toy soldiers to Trivial Pursuit.
Includes bibliographical references (p. 135-136).
Keywords: Toys -- History -- Juvenile literature; Inventions -- History -- Juvenile literature; Toys; Inventions